2016
DOI: 10.1007/s11060-016-2173-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-132 targets PEA-15 and suppresses the progression of astrocytoma in vitro

Abstract: Gliomas are highly malignant tumors, the most common of which are astrocytomas. A growing number of studies suggest that dysregulation of miRNAs is a frequent event contributing to the pathogenesis of gliomas. In this study, we found that over-expression of miR-132 inhibited cell proliferation and migration and triggered apoptosis, while knockdown of miR-132 showed opposite effects. PEA-15 was identified as a direct target of miR-132. Reintroduction of PEA-15 without 3'UTR region reversed the inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…However, studies on its effect in glioma were not too much. Some studies proved that miR-132 was an anti-oncogene that inhibited migration and invasion of glioma [ 39 , 40 ]. Nevertheless, its target relationship with NEAT1 has never been revealed except for this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on its effect in glioma were not too much. Some studies proved that miR-132 was an anti-oncogene that inhibited migration and invasion of glioma [ 39 , 40 ]. Nevertheless, its target relationship with NEAT1 has never been revealed except for this study.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, CREB can be either target for specific miRNAs or modulator for miRNAs expression. By using the luciferase reporter system and real time PCR, Geng and coworkers identified CREB and KLF as a functional upstream regulator of the tumor suppressor miR-132 in U87 and U251 astrocytoma cells [98]. On the contrary, CREB abrogation by miR-1224-5p and miR-200b suppresses glioma progression in preclinical models [99,100].…”
Section: Creb and Brain Cancermentioning
confidence: 99%
“…Mechanistic explorations in this study revealed that NEDD4 enhances the binding ability of KLF8 to the miR-132 promoter region and represses expression of miR-132. The transcription factor KLF8 was highlighted in a previously conducted study to modulate the expression of miR-132, which plays an important role in the tumorigenesis of astrocytoma 14 . Prior evidence has documented that the modulation of the miR-132/Sox5 signaling pathway by circDOCK1 affects the migration potential of bladder cancer cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KLF8 is a transcription factor in the Sp/KLF family and has a pivotal role in cancer metastasis by stimulating the proliferation and migratory ability of bladder cancer cells 13 . KLF8 has been confirmed as a transcription factor of microRNA-132 (miR-132), and KLF8 can modulate the expression of miR-132 to exert functions in astrocytoma 14 . In bladder cancer, overexpressed levels of miR-132 were shown to restrict the migratory and invasive capacities of tumor cells and play a suppressive role in metastasis 15 .…”
Section: Introductionmentioning
confidence: 99%